1993
DOI: 10.1159/000196166
|View full text |Cite
|
Sign up to set email alerts
|

From Not Detected Pulmonary Embolism to Diagnosis of Chronic Thromboembolic Pulmonary Hypertension: A Retrospective Study

Abstract: The past and present clinical history of 13 patients with hemodynamic and angiographic diagnosis of chronic thromboembolic pulmonary hypertension (CTPH) was reviewed in order to investigate the reasons for failure of resolution of acute pulmonary embolism (PE) and findings useful for diagnosis of CTPH. All patients had chest radiograph, ECG, arterial blood gas analysis and pulmonary perfusion scintigraphy performed. Clinical assessment demonstrated that no patient had diagnosis and treatment of the several ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Only PTE may be performed, even in high-risk patients. Moreover, PALLA et al [32] showed that the patients with CTEPH usually had no diagnosis and treatment for the several retrospectively identified episodes of pulmonary embolism. Our future goals will be to improve the diagnosis and treatment of pulmonary embolism, and to further improve diagnostic accuracy of chronic thromboembolic pulmonary hypertension and surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Only PTE may be performed, even in high-risk patients. Moreover, PALLA et al [32] showed that the patients with CTEPH usually had no diagnosis and treatment for the several retrospectively identified episodes of pulmonary embolism. Our future goals will be to improve the diagnosis and treatment of pulmonary embolism, and to further improve diagnostic accuracy of chronic thromboembolic pulmonary hypertension and surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Patient #6 of Table 1 was a ventriculo-atrial shunt carrier and had experienced shunt infection and thrombosis ten years prior to the diagnosis. Taken together, the time lapse between the potential initiating event and the diagnosis is hard to estimate for the whole group (13), and lies anywhere between 1.5 and ten years.…”
Section: Clinical Assessmentmentioning
confidence: 99%